The wake wash prediction on an asymmetric catamaran hull form - Yaakob, Omar; Abd. Ghani, Pauzi; Abd. Mukti, Mohd. Afifi; Nasirudin, Ahmad; Tawi, Kamarul Baharin; Mat Lazim, Tholudin (2006)
This paper presents results of wake wash prediction on an asymmetric catamaran hull form for leisure craft application. The study seeks to find the effect of hull form configuration and separation to length ratio on wave height produced. Computational Fluid Dynamics simulation was carried out and the results indicate that a novel method of arrangement of the catamaran demihulls as well as their spacing improves the wake-wash characteristics significantly.